2009
DOI: 10.1080/19346182.2009.9648509
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glove type on wheelchair rugby sports performance

Abstract: The aim of the present study was to determine the effects of a selection of gloves currently used by wheelchair rugby players upon aspects of skill performance. Eleven able-bodied male participants on two separate occasions performed three rugby-specific drills in four glove conditions: building (BLD), multipurpose (MLP) and US National Football League (NFL) gloves and no gloves (NO). A series of one-way ANOVA with repeated measures were performed to evaluate the different outcomes. No significant influence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…The present study is in agreement with previously published research where performance in sports has been shown to improve with the use of a glove (Lewis et al, 2014;Lutgendorf et al, 2009). With similar results to the present study, where the researchers displayed a significant increase in CHS and BS, Lutgendorf et al (2009) showed that the use of a glove in wheelchair rugby significantly increased acceleration compared to the bare hand. In addition to this, during ultimate frisbee, Lewis et al (2014) reported that using a glove when catching the frisbee increased friction and, therefore, increased performance during the execution of the skill.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present study is in agreement with previously published research where performance in sports has been shown to improve with the use of a glove (Lewis et al, 2014;Lutgendorf et al, 2009). With similar results to the present study, where the researchers displayed a significant increase in CHS and BS, Lutgendorf et al (2009) showed that the use of a glove in wheelchair rugby significantly increased acceleration compared to the bare hand. In addition to this, during ultimate frisbee, Lewis et al (2014) reported that using a glove when catching the frisbee increased friction and, therefore, increased performance during the execution of the skill.…”
Section: Discussionsupporting
confidence: 93%
“…For example, during wheelchair rugby the use of gloves is promoted to increase the friction between the hand and wheelchair. Lutgendorf et al (2009) showed that the use of an NFL glove significantly increased acceleration and agility compared to various other gloves and therefore increased performance of the athlete. It was found that, acceleration and agility were also reduced when athletes did not wear a glove (bare hand).…”
Section: Introductionmentioning
confidence: 99%
“…This translated to improved hitting distance and accuracy, though only for those shots using the longer clubs. Gloves are also used in wheelchair‐based sports, as they enable the athlete to significantly increase their acceleration and agility [42].…”
Section: Managing Skin Tribology To Enhance Sporting Performancementioning
confidence: 99%